THE WORD FORMATION PROCESS IN RICK RIORDAN’S NOVEL ENTITLED “PERCY JACKSON AND THE OLYMPIANS: THE LIGHTNING THIEF” - Wulandary, Dewi; Abdullah, Ahmad Rizal; Syamsuddin, Rifqi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research aims to find out the kind of word formation processes used in Rick Riordan's Novel entitled “Percy Jackson and The Olympians: The Lightning Thief” based on George Yule's (2010) theory. We use qualitative method by collecting the selected words that are classified into the kind of word formation. The results of this research show that thirty data are classifying the kinds of word formation processes based on George Yule and the data will be described descriptively. There were 10 kinds of word formation based on the theory of George Yule. They were Borrowing (3), Compounding (2), Blending (1), Clipping (2), Acronym (1), Derivation (2), Multiple Process (1). Based on the data above, the researcher concludes that the dominant kinds of word formation found in the novel Percy Jackson and The Olympians: The Lightning Thief is Borrowing.